Duration of support and financial health of business support structures in Burkina Faso, Cameroon, and Ghana: A micro-econometric analysis - Jean C. Kouam; Simplice Asongu; Bin Joachem Meh; Robert Nantchouang; Fri L. Asanga; Denis Foretia (African Governance and Development Institute (AGDI), 2022)
Access to finance is perceived as one of the major problems facing businesses in Sub-Saharan Africa, as well as the structures that support them in their development. This paper aims to measure the probability that a support structure with given characteristics, specific services to entrepreneurs and some technical capacities will face large-scale financial problems. We estimate a multinomial logistic model using a pool of disaggregated data collected by the Nkafu Policy Institute in a survey of 79 business support structures in Burkina Faso, Cameroon and Ghana in 2021. Our results show that the financial health of a business support structure is not fundamentally dependent on the duration of support, but rather on other factors related to the quality of services offered to entrepreneurs.
Keywords: C13; C25; M20; O10; O30; O55; 330; Duration of support; Financial Health of Businesses; Sub-Saharan Africa; Multinomial logit model